The Role of Keynesians in Wartime Policy and Postwar Planning, 1940-1946 - Jones, Byrd L. (American Economic Review, 1972)
Early in 1940, Secretary of Commerce Harry Hopkins showed Franklin Roosevelt a brief outline of fiscal policies for defense as seen by economists on his staff. The first step was prompt expansion to the level of full by means of federal deficits. Then, once full employment is attained, the task of fiscal policy is twofold: (1) to maintain full employment; (2) to secure as rapidly as possible that orientation of production which our defense demands. Leon Henderson, Richard V. Gilbert, and other liberal Keynesian advisers were proceeding with the 1930's agenda of recovery. They viewed expenditures for national defense, together with exports of military goods, as